Tracheocutaneous Sinus following Tracheocutaneous Fistula Repair: Management Strategies in a Pediatric Patient - Bender-Heine, Adam (Case Rep Otolaryngol, 2018)
OBJECTIVE: To present a rare case of a pediatric tracheocutaneous sinus years after repair of a tracheocutaneous fistula and to review management strategies. BACKGROUND: A tracheocutaneous fistula is a common sequela of pediatric tracheostomy and can occur in as many as one in three pediatric patients. There is debate in the literature regarding optimal surgical management. CASE PRESENTATION: An 8-year-old girl presented to the emergency department with swelling and erythema over the anterior neck. Clinical exam and diagnostic imaging revealed an underlying tracheocutaneous sinus. DISCUSSION: Complications following pediatric tracheostomy are common and range in complexity from stomal granulation to tracheocutaneous fistula. There is some debate regarding the optimal surgical management of children with tracheocutaneous fistula following tracheostomy. This report discusses the management of a pediatric child with an unusual tracheocutaneous sinus and reviews the various surgical techniques which have been described for definitive repair.